Treatment delivery of the community reinforcement approach in outpatient addiction treatment. (October 2018) - Kraan, Anneleen E.M.; Dijkstra, Boukje A.G.; Markus, Wiebren
Highlights: How often therapists deliver CRA procedures in treatment sessions varies considerably. The degree to which all separate CRA procedures are used, also varies strongly among therapists. Procedures involving behavioral skills training are used less frequently. The delivery of several CRA procedures is affected by advanced training. The delivery is also affected by experienced difficulty and meaningfulness. Abstract: Objective: Treatment model adherence is an important predictor of treatment outcome. In clinical practice evidence-based treatments are delivered in widely varying degrees. This study examines which Community Reinforcement Approach (CRA) procedures are delivered by addiction care therapists and how this is associated with therapist characteristics. Method: The study integrated two observational designs. Firstly, using a prospective design, 24 therapists registered every CRA procedure delivered during every patient contact over a six month period. Secondly, using a cross-sectional design, personal characteristics of 69 therapists were assessed including their self-reported delivery of CRA procedures and their perceptions with regard to the meaningfulness and complexity of these procedures. Results: The number of CRA procedures delivered varied substantially among therapists both at session and patient level. More experienced therapists and those that had received advanced training previously, delivered more CRA procedures. Finally, the delivery of CRA procedures was positively associated with experienced meaningfulness and negatively associated with difficulty. Conclusions: The results confirm the relation between treatment delivery and experienced meaningfulness and difficulty of CRA procedures and provides support for advanced training to enhance the delivery of a wider range of CRA procedures.